2023
DOI: 10.1177/19458924221149267
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Rhinitis in Preschoolers: A Systematic Review of Diagnostics

Abstract: Background Most studies that seek to analyze the prevalence of allergic rhinitis do not include preschool children and the diagnosis in this age group is difficult. Objective Identify complementary tests to the diagnosis of allergic rhinitis in preschool children and verify if there is scientific robustness to propose a diagnostic algorithm for this condition in this age group. Methods Systematic review of the literature in four databases: SCIELO, PubMed/MEDLINE, LILACS and SCOPUS. Each article was initially c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Lastly, Diniz et al identified difficulties in diagnosing allergic rhinitis in preschool children. 15 To elucidate a better definition, they performed a systematic review and found nasal cytology, serum-specific IgE, and skin tests were the most used test. However, a lack of a reliable diagnostic algorithm exists and would be an important area to focus future research.…”
mentioning
confidence: 99%
“…Lastly, Diniz et al identified difficulties in diagnosing allergic rhinitis in preschool children. 15 To elucidate a better definition, they performed a systematic review and found nasal cytology, serum-specific IgE, and skin tests were the most used test. However, a lack of a reliable diagnostic algorithm exists and would be an important area to focus future research.…”
mentioning
confidence: 99%